Representações sobre as práticas educativas de qualificação profissional em serviço de trabalhadores da enfermagem de uma unidade hospitalar - Adriane dos Santos Nunes Anacker; Moacir Fernando Viegas (Centro Universitário Salesiano de São Paulo, 2016)
The article has its roots on a research that had as main goal to describe, analyze and comprehend the representations of nurses and nursing technicians of a hospital unit regarding the educative practices of professional qualification realized within their workplace. The theme lies in the field of the relations between work, health and education. The relevance and topicality of the theme relate with the constant need of thinking about educational practices at work in a context of deep changes in the service production in health. The study characterizes as a qualitative research with historical-critic approach. As tools were used semi structured interviews and field observations. The results describe the educational practices mad within the institution that was object of the study, its limitations and possibilities.